Design and Validation of an Observational System for Penalty Kick Analysis in Football (OSPAF) - Pinheiro, Guilherme de Sousa; Nascimento, Vitor Bertoli; Dicks, Matt; Costa, Varley Teoldo; Lames, Martin (Frontiers in Psychology, 2021)
The analysis of penalty kick has played an important role in performance analysis. The study aims are to get formal feedback on the relevance of variables for penalty kick analysis, to design and validate an observational system; and to assess experts’ opinions on the optimum video footage in penalty kick analysis. A structured development process was adopted for content validity, reliability, and agreement on video usage. All observational variables included in OSPAF showed Aiken's V values above the cut-off (for 5-scale V > 0.64; for 2-scale = V > 0.75; p<0.05). Cohen’s Kappa resulted in mean intra- and inter-rater reliability values of 0.90 and 0.86, respectively. It is recommended to combine at least 3 different viewing angles (V = 0.90; p= 0.006) with standardization of video quality (V = 0.95; p = 0.006). Changing the viewing angles may influence the observer perception (V = 0.86; p= 0.006). The aerial and pitch-level viewing angle behind the penalty taker and pitch-level viewing angle behind the goalkeeper were indicated as most appropriate for observational analysis (V = 0,97; p = 0.01). The OSPAF met all requirements of instrument validation. It may be recommended as the basis of future observational systems on penalty kicks.